STRATEGI MARKETING PUBLIC RELATIONS LARISSA SKIN CARE & HAIR TREATMENT YOGYAKARTA DALAM MEMPERTAHANKAN DAN MENINGKATKAN CITRA BACK TO NATURE - Putri, Andryani Handrayani; Lestari, Puji; Prabowo, Agung (Jurnal Ilmu Komunikasi, 2009)
Appereance to support confidence into one of public attention both old and young, men and woman. This causes more and more beauty centers that complete in the market. On is Larissa Skin Care & Hair Treatment established in 1984 until now still retain the concept of natural or Back To Nature, although the development Larissa improve the quality of products and services, offset by the use of technologies that are new and modern. The research aims ti identify strategies Larissa Marketing Public Relations Skin Care & Hair Treatment Yogyakarta in maintaining and improving the image of Back to Nature. Framework of thought reffered to the Marketing and Public Relations to obtain a positive image in society. Marketing Public Relations Strategy is used innovation strategy, Driving Market Strategies, Electronic PR (E-PR), anf Media Relations. In addition Larissa also use various promotional tools that can support the the acitivities of Marketing and Public Relations for the intended message can be up to the public. Influence of advertising, collaboration, word of mouth promotion, and Public Relations Marketing activities through programs and mass media helps in improving the image of Back To Nature Larissa. Larissa is currently still the only center of the concept of natural beauty this become a major force for competition in the field or beauty. The results showed that the strategy of Public Relations Marketing Larissa Skin Care and Hair Treatment Yogyakarta able to main- tain and improve the image of Back To Nature.